Is there a Role for Antenatal Corticosteroids in Term Infants before Elective Cesarean Section? - Augusta Arruda; Mariana Ormonde; Sarah Stokreef; Beatriz Fraga; Catarina Franco; Catarina Dâmaso; Ana Lima (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective Cesarean section (CS) delivery, especially without previous labor, is associated with worse neonatal respiratory outcomes. Some studies comparing neonatal outcomes between term infants exposed and not exposed to antenatal corticosteroids (ACS) before elective CS revealed that ACS appears to decrease the risk of respiratory distress syndrome (RDS), transient tachypnea of the neonate (TTN), admission to the neonatal intensive care unit (NICU), and the length of stay in the NICU. Methods The present retrospective cohort study aimed to compare neonatal outcomes in infants born trough term elective CS exposed and not exposed to ACS. Outcomes included neonatal morbidity at birth, neonatal respiratory morbidity, and general neonatal morbidity. Maternal demographic characteristics and obstetric data were analyzed as possible confounders. Results A total of 334 newborns met the inclusion criteria. One third of the population study (n=129; 38.6%) received ACS. The present study found that the likelihood for RDS (odds ratio [OR]=1.250; 95% confidence interval [CI]: 0.454-3.442), transient TTN (OR=1.,623; 95%CI: 0.556-4.739), and NIUC admission (OR=2.155; 95%CI: 0.474-9.788) was higher in the ACS exposed group, although with no statistical significance. When adjusting for gestational age and arterial hypertension, the likelihood for RDS (OR=0,732; 95%CI: 0.240-2.232), TTN (OR=0.959; 95%CI: 0.297--3.091), and NIUC admission (OR=0,852; 95%CI: 0.161-4.520) become lower in the ACS exposed group. Conclusion Our findings highlight the known association between CS-related respiratory morbidity and gestational age, supporting recent guidelines that advocate postponing elective CSs until 39 weeks of gestational age.